2017
DOI: 10.1007/978-3-319-53925-6_8
|View full text |Cite
|
Sign up to set email alerts
|

A Width Parameter Useful for Chordal and Co-comparability Graphs

Abstract: Belmonte and Vatshelle (TCS 2013) used mim-width, a graph width parameter bounded on interval graphs and permutation graphs, to explain existing algorithms for many domination-type problems on those graph classes. We investigate new graph classes of bounded mim-width, strictly extending interval graphs and permutation graphs. The graphs K t K t and K t S t are graphs obtained from the disjoint union of two cliques of size t, and one clique of size t and one independent set of size t respectively, by adding a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Furthermore, for each fixed integer k ≥ 1, the k-domination and total k-domination problems are solvable in time O(n 6k+4 ) in the class of interval graphs where n is the order of the input graph. This follows from recent results due to Kang et al [41], building on previous works by Bui-Xuan et al [8] and Belmonte and Vatshelle [3]. In fact, Kang et al studied a more general class of problems, called (ρ, σ)-domination problems, and showed that every such problem can be solved in time O(n 6d+4 ) in the class of n-vertex interval graphs, where d is a parameter associated to the problem (see Corollary 3.2 in [41] and the paragraph following it).…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, for each fixed integer k ≥ 1, the k-domination and total k-domination problems are solvable in time O(n 6k+4 ) in the class of interval graphs where n is the order of the input graph. This follows from recent results due to Kang et al [41], building on previous works by Bui-Xuan et al [8] and Belmonte and Vatshelle [3]. In fact, Kang et al studied a more general class of problems, called (ρ, σ)-domination problems, and showed that every such problem can be solved in time O(n 6d+4 ) in the class of n-vertex interval graphs, where d is a parameter associated to the problem (see Corollary 3.2 in [41] and the paragraph following it).…”
Section: Introductionsupporting
confidence: 85%
“…The approach of Kang et al [41], which implies that k-domination and total k-domination are solvable in time O(|V (G)| 6k+4 ) in the class of interval graphs also works for the weighted versions of the problems, where each vertex u ∈ V (G) is equipped with a non-negative cost c(u) and the task is to find a (usual or total) k-dominating set of G of minimum total cost. For both families of problems, our approach can also be easily adapted to the weighed case.…”
Section: The Weighted Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kang et al [39] also proved that the classes of chordal graphs, circle graphs and co‐comparability graphs have unbounded mim‐width; for the latter two classes, this was shown independently by Mengel [43]. Vatshelle [49] and Brault‐Baron et al [13] showed the same for grids and chordal bipartite graphs, respectively, whereas Mengel [43] proved that strongly chordal split graphs have unbounded mim‐width.…”
Section: Introductionmentioning
confidence: 98%
“…Let Kr0.25em0.25emKr be the graph obtained from 2Kr by adding a perfect matching, and let Kr0.25em0.25emrP1 be the graph obtained from Kr0.25em0.25emKr by removing all the edges in one of the complete graphs (see Section 2 for undefined notation). Kang et al [39] showed that for any integer r2, there is a polynomial‐time algorithm for computing a branch decomposition of mim‐width at most rinfixafter−1 when the input is restricted to (Kr0.25em0.25emrP1)‐free chordal graphs, which generalize interval graphs, or (Kr0.25em0.25emKr)‐free co‐comparability graphs, which generalize permutation graphs. Hence, in particular, all these classes have bounded mim‐width.…”
Section: Introductionmentioning
confidence: 99%